Electrocatalytic properties of N-doped graphite felt in electro-Fenton process and degradation mechanism of levofloxacin. (September 2017) - Liu, Xiaocheng; Yang, Danxing; Zhou, Yaoyu; Zhang, Jiachao; Luo, Lin; Meng, Sijun; Chen, Song; Tan, Mengjiao; Li, Zhicheng; Tang, Lin
Abstract: The degradation of antibiotic levofloxacin was investigated by dimensionally stable anode as well as modified cathode using low-cost chemical reagents of hydrazine hydrate and ethanol for electro-Fenton in an undivided cell at pH 3.0 under room temperature. Comparison of unmodified and modified cathode was performed. The apparent rate constant of levofloxacin decay was found to be 0.2883 min −1 for graphite felt-10 with the best performance at 200 mA, which is lower than graphite felt at 400 mA. The optimum modified cathode showed a significant improvement of complete mineralization of levofloxacin, reaching a 92% TOC removal at 200 mA for 480 min higher than unmodified one at twice the current. Surface physicochemical properties and morphology were investigated by scanning electron microscope, contact angle and X-ray photoelectron spectroscopy. The electrochemical characterization of hydrogen evolution reaction was adopted to clarify a possible pathway for the higher mineralization of levofloxacin, indicating a potential pilot-scale study to the pollution with the similar structure. Graphical abstract: Highlights: N-doped graphite felt increase the total mineralization of electro-Fenton process. The increase HER clarified mechanism of higher mineralization of levofloxacin. The stability of levofloxacin and intermediates was affected by side chain. Low-cost strategies have considerable efficiency for potential pilot-scale study.